An Evaluation of the Long-Term Stagnancy of Porewater in the Neogene Sedimentary Rocks in Northern Japan. (18th January 2018) - Nakata, Kotaro; Hasegawa, Takuma; Oyama, Takahiro; Ishii, Eiichi; Miyakawa, Kazuya; Sasamoto, Hiroshi
Abstract : A groundwater dating for very old porewater using 36 Cl and 4 He was applied to the Koetoi and Wakkanai formations distributed in the northernmost part in Japan. Measured 36 Cl/Cl in the Koetoi Formation was 2.6 ± 2.0 × 10 −15 and that in the Wakkanai Formation was 8.1 ± 2.5 × 10 −15 . These values are similar to 36 Cl/Cl in situ secular equilibrium calculated from chemical compositions of core suggesting that Cl − ions and porewater have remained in the formations for much longer than half-life of 36 Cl . He concentration in porewater ranged from 1.1 × 10 −6 to 2.6 × 10 −5 (c c S T P   g w - 1 ) and it is much higher than water saturated with air indicating that both formations contain very old porewater. However, the possibility of mixing of young water was indicated because He concentration was lower than that calculated by multiplication of in situ He production and time after the uplift. This possibility was also supported by Cl −, δ D, and δ 18 O data. After combining information on 36 Cl/Cl, 4 He, and δ D and δ 18 O, it was inferred that the porewater in the deep part of the Wakkanai Formation might have been stagnant since the uplift. The porewater in the Koetoi Formation and the shallow part of the Wakkanai Formation were found to be affected by young surface water.